The bad guys in Alien vs. Bad Guys - Blabey, Aaron (New York, NY Scholastic Inc, 2018)
A creature with tons of teeth and way too many butts is stealing the Bad Guys one by one.--Provided by Publisher
English stories
First published in 2017
Accelerated Reader AR
Keywords: Extraterrestrial beings -- Juvenile fiction; Kidnapping -- Juvenile fiction; Extraterrestrial beings -- Fiction; Humorous stories; Animals -- Fiction; Extraterrestrial beings; Heroes -- Fiction; Humorous fiction; JUVENILE FICTION -- Action & Adventure -- General; JUVENILE FICTION -- Animals -- General; JUVENILE FICTION -- Humorous Stories; Kidnapping; Monsters -- Fiction; Space travel -- Fiction; Children's stories; Graphic Novel; Fiction; Graphic novels; Graphic novels; Humorous fiction; Humorous fiction; Humorous fiction; Humorous graphic novels; Juvenile works